Metals in sugarcane molasses wastewater subjected to thermophilic anaerobic digestion - Yabuki, Lauren N. M. [UNESP]; Da Silva, Camila M. R. [UNESP]; Oliveira, Cristiane A.; Menegário, Amauri A. [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Taylor & Francis, 2020)
This study evaluated the occurrence and removal of eleven trace elements, B, Co, Cu, Fe, Mn, Mo, Ni, Se, V, W and Zn, from sugarcane molasses wastewater through a thermophilic anaerobic structured-bed reactor (AnSTBR). Concentration ranges in molasses were, in μg. L−1: 19–277; 6–18; 37–449; 155–2160; 26–392; 3–15; 6–41; 12–46; 6–31; and 25–1648; for B, Co, Cu, Fe, Mn, Mo, Ni, Se, V, and Zn, respectively. Tungsten was not identified in the molasses. The average metal/nutrient removal efficiency was 62 ± 12, 58 ± 22, 55 ± 28, and 49 ± 12% for selenium, manganese, molybdenum, and iron, respectively. It is possible that the overall anaerobic digestion functioning is not affected up to these reported metal values. Environmental impacts from releasing effluent streams into soils and groundwater need to be investigated.
Keywords: anaerobic digestion; Metal removal; sugarcane molasses